(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
This study investigates the impact of using a techno-organic education paradigm in primary reading and writing teaching on students’ academic progress and attitudes, particularly using Makey Makey kit applications, and solicits feedback from educators and students. The quantitative part of the research sample comprises of first-grade kids from a rural school in the Ceylanpnar district of Anlurfa. The quantitative dimension research group consists of 35 kids identified by the group matching approach. In contrast, the qualitative dimension study group comprises the experimental group of students, their parents, and classroom teachers. While the experimental group used the Makey Makey kit to instruct, the control group proceeded with the present curriculum. One of the mixed-method designs employed in the study was the explanatory sequential mixed method design. In the quantitative component of the research, a quasi-experimental design was utilized, and in the qualitative dimension, a phenomenology design was used. According to the data analysis findings for the quantitative component of the study, a statistically significant difference in the accomplishment tests of the experimental and control groups was discovered in favor of the experimental group. According to the results, students’ attitudes toward the techno-organic education paradigm and the Makey Makey kit were favorable, drawing students’ interest and enhancing their enthusiasm to study.